A comparative study on the effectiveness of TiN, TiCN, and AlTiN coated carbide tools for dry micro-milling of aluminium, copper and brass at low spindle speed. (2018) - Jahan, Muhammad P.; Arbuckle, Gregory K.; Rumsey, Ann M.
The objective of this study is to investigate the effectiveness of titanium nitride (TiN), titanium carbo-nitride (TiCN), and aluminium titanium nitride (AlTiN) coatings on the tungsten carbide (WC) cutting tool for minimising the tool wear and tool breakage during dry micro-milling of aluminium, copper and brass at lower spindle speed. A comparative analysis on the machining speed, surface finish and tool wear were carried out for machining three materials using uncoated and coated carbide tools. The TiN coated tools were found to produce comparatively smoother surface finish in all three materials. The TiN coating was effective in the reduction of tool wear during micro-milling at higher feed rate and depth of cut, making it suitable for faster machining. Among three materials, brass produced superior surface finish, followed by aluminium and copper. Considering all the performance indicators, brass exhibited superior machinability than copper and aluminium in micro-milling for both coated and uncoated carbide tools.